DEVELOPMENT OF ARTSTEPS-BASED MEDIA AS AN INFORMATION SERVICE TO PREVENT BULLYING BEHAVIOR IN STUDENTS AT SMA NEGERI 3 PALANGKA RAYA - Nurul Asti Seftiana; Fendahapsari Singgih Sendayu; Nonsihai; Herda Fitri Br Ginting (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to develop Artsteps-based media as an informational service to prevent bullying behavior. The research adopts a Research and Development (RnD) approach using the Borg and Gall model, which has been simplified into three stages: the pre-development stage, which includes Research and Information Collecting; the development stage, which involves the Development of a Preliminary Form of Product; and the post-development stage, consisting of Preliminary Field Testing and Main Product Revision. The subjects of the product testing and development were evaluated by one media expert, one Guidance and Counseling expert, and two practitioner experts as validators, analyzed using Aiken’s V. The evaluation results from the media expert were 1.00, the Guidance and Counseling expert 1.08, and the practitioner experts 1.18, each indicating a high level of relevance. These scores were calculated based on the coefficient values of each aspect. The results demonstrate that the Artsteps application media is suitable for use as an informational service to prevent bullying behavior based on aspects of acceptability.